Mediation in the accompaniment of students and parents in a digital context - Chávez, Harol (2021)
In this research, the review of scientific articles on mediation in virtual teaching in situations of new educational experience was analyzed through a systematic study of specialized literature related to mediation in the accompaniment of students and parents in a digital context. The research design used is qualitative through documentary analysis. Specialized references and documents were handled in different types of data platforms and search equations. The study focused on the mediation category and four emerging subcategories: Mediation as a pedagogical method, a mediation tool for teaching, digital families and the mediator in the educational process, a comparison of exploration topics was made between mediation for teaching and shared responsibilities in learning. By way of conclusion, we can mention that the mediation was a means of pedagogical accompaniment for the students and their families.